Citation Impact of ‘Letter to the Editor’ Published by Indian Scientists in Journals Indexed by Science Citation Index Expanded (SCIE) - Garg, K.C.; Kumar, Suresh (DESIDOC Journal of Library & Information Technology, 2013)
An analysis of letters published by top 10 publishing countries in journals indexed by Science CitationIndex Expanded (SCIE) during 1987-89, 1997-99 and 2007-09 indicates that the letters published bydeveloped countries including China have declined as proportion of their total output. The number ofletters published by Indian scientists has remained constant during the three blocks. These letters werescattered in a large number of journals published from advanced countries of the world and India. Theletters came from more than 1000 institutions located in different parts of the country. The highest numberof letters was published in the discipline of medicine and the letters published in the fi eld of chemistry had the highest Relative Citation Impact (RCI). http://dx.doi.org/10.14429/djlit.33.1.3732